Construction of therapeutic group spaces during hospitalization: experience in a medium-stay unit in the ciudad autónoma de buenos aires - Tononi, Rosana; Dawidoski, Adriana; Vicens, Jimena; Díaz, Morena; Ventriglia, Irene (Revista del Hospital Italiano de Buenos Aires, 2018)
This experience report describes the development of a socialization group device in the approach of complex patients in rehabilitation from 2016 on a Medium-Stay Unit (MSU) of the Hospital Italiano de Buenos Aires. It started by recognizing the possibility of working within the social psychology framework of Pichon-Rivière by adapting the technique of the operative group for hospital environments with high level of stress, defunctionalization and disruption of daily life. In this report we describe the conformation in this MSU of therapeutic operative groups of patients with physical, cognitive or palliative care impairment. The methodology for the analysis was based on the prospective narrative record of each group meeting. We present a theoretical reflection on the adaptations to the framing and the planning of each group activity. This allowed us to achieve continuity and group belonging in the operative groups developed in this hospital context
Keywords: comprehensive health care; social psychology; socialization; Argentina